Anomalously low modulus of the interpenetrating-phase composite of Fe and Mg obtained by liquid metal dealloying. (1st April 2019) - Okulov, I.V.; Geslin, P.-A.; Soldatov, I.V.; Ovri, H.; Joo, S.-H.; Kato, H.
Abstract: A bulk interpenetrating-phase composite consisting of immiscible Fe and Mg metals is fabricated by liquid metal dealloying. The composite exhibits an anomalously low value of the Young's modulus of 20 ± 3 GPa, when probed in compression. The Young's modulus values obtained from nanoindentation and ultrasonic measurements are, however, significantly higher than that in compression, but still remain lower than theoretical values obtained from the Hashin-Shtrikman bounds and a micromechanics model. Such a deviation is explained by the weak interfaces between Fe and Mg phases that promote phase boundary sliding upon mechanical loading, leading to a low effective modulus. Graphical abstract: Unlabelled Image